Macrophages treated with antigen from the tapeworm Hymenolepis diminuta condition CD25+ T cells to suppress colitis. Issue 4 (22nd January 2019) - Reyes, José L.; Lopes, Fernando; Leung, Gabriella; Jayme, Timothy S.; Matisz, Chelsea E.; Shute, Adam; Burkhard, Regula; Carneiro, Matheus; Workentine, Matthew L.; Wang, Arthur; Petri, Björn; Beck, Paul L.; et al.
ABSTRACT: Macrophages play central roles in immunity as early effectors and modulating adaptive immune reponses; we implicated macrophages in the anticolitic effect of infection with the tapeworm Hymenolepis diminuta . Here, gene arrays revealed that H. diminuta antigen (HdAg) evoked a program in murine macrophages distinct from that elicited by IL‐4. Further, HdAg suppressed LPS‐evoked release of TNF‐α and IL‐1β from macrophages via autocrine IL‐10 signaling. In assessing the ability of macrophages treated in vitro with an extract of H. diminuta [M (HdAg) ] to affect disease, intravenous, but not peritoneal, injection of M (HdAg) protected wild‐type but not RAG1 −/− mice from dinitrobenzene sulphonic acid (DNBS)‐induced colitis. Administration of splenic CD4 + T cells from in vitro cocultures with M (HdAg), but not those cocultured with M (IL‐4) cells, inhibited DNBS‐induced colitis; fractionation of the T‐cell population indicated that the CD4 + CD25 + T cells from cocultures with M (HdAg) drove the suppression of DNBS‐induced colitis. Use of IL‐4 −/− or IL‐10 −/− CD4 + T cells revealed that neither cytokine alone from the donor cells was essential for the anticolitic effect. These data illustrate that HdAg evokes a unique regulatory program in macrophages, identifies HdAg‐evoked IL‐10 suppression of macrophage activation, and reveals the ability of HdAg‐treated macrophages to educate ( i.e ., condition) and mobilize CD4 + CD25 + T cells, which could be deployed to treat colonic inflammation.—Reyes, J. L., Lopes, F., Leung, G., Jayme, T. S., Matisz, C. E., Shute, A., Burkhard, R., Carneiro, M., Workentine, M. L., Wang, A., Petri, B., Beck, P. L., Geuking, M. B., McKay, D. M., Macrophages treated with antigen from the tapeworm Hymenolepis diminuta condition CD25 + T cells to suppress colitis. FASEB J. 33, 5676–5689 (2019). www.fasebj.org